Content validation of the SF-36v2® health survey with AL amyloidosis patients - Michelle K. White; Martha S. Bayliss; Spencer D. Guthrie; Kimberly P. Raymond; Avery A. Rizio; Kristen L. McCausland (SpringerOpen, 2017)
Abstract Background This study examined the content validity of the SF-36v2® Health Survey (SF-36v2) in patients with AL amyloidosis using qualitative interviews with physicians and patients. The study included three distinct phases of qualitative research: concept elicitation interviews among physicians, concept elicitation interviews among patients, and cognitive debriefing interviews among patients. The concept elicitation interviews focused on areas of health-related quality of life that are affected by AL amyloidosis and may be affected by treatment, while patient cognitive debriefings aimed to confirm whether the SF-36v2 instructions, recall period, items, and response choices were comprehensive and understandable to AL amyloidosis patients. Results Physicians discussed the importance of measuring physical functioning, general health, mental/emotional health, sleep, fatigue, and work impact; though they also reported that they do not routinely use a standard Patient-Reported Outcome (PRO) measure of health-related quality of life. Patients described social, physical, role, and emotional impacts of AL amyloidosis and various treatments. Cognitive debriefing interviews confirmed the relevance of the concepts measured by the SF-36v2 and indicated that patients found the SF-36v2 both easy to understand and complete, that the SF-36v2 instructions and items were comprehensive and understandable without change, and the response choices and recall period were appropriate for use with patients with AL amyloidosis. Conclusions The findings support the content validity of the SF-36v2 as an appropriate measure of health-related quality of life in patients with AL amyloidosis.